Crystal structure of 2-((2,8-bis(trifluoromethyl)quinolin-4-yl)(hydroxy)methyl)piperidin-1-ium trifluoroacetate, [C17H17F6N2O][C2F3O2] - Wardell, James L.; Tiekink, Edward R. T. * (de Gruyter, 2019)
[C17H17F6N2O][C2F3O2], triclinic, P¯1 (no. 2), a = 7.9873(1) Å,b = 11.0534(2) Å, c = 13.2380(3) Å, α = 105.617(1)°, β = 102.189(1)°, γ = 106.075(1)°. V = 1028.76(3) Å3 , Z = 2,Rgt(F) = 0.0403, wRref(F2) = 0.1086, T = 120(2) K. CCDC no.: 1895037 The title crystal structure is shown in the figure. Tables 1 and 2 contain details on crystal structure and measurement conditions and a list of the atoms including atomic coordinates and displacement parameters.